Metal bioavailability to Eisenia fetida through copper mine dwelling animal and plant litter, a new challenge on contaminated environment remediation. (September 2016) - Nirola, Ramkrishna; Megharaj, Mallavarapu; Saint, Christopher; Aryal, Rupak; Thavamani, Palanisami; Venkateswarlu, Kadiyala; Naidu, Ravi; Beecham, Simon
Abstract: The feeding on dead and decaying matter (detritus) by earthworms was evaluated to find if there are environmental challenges of animal faecal matter and plant litter. The control soils were used as reference to calculate bioaccumulation factor and determine soluble and bioavailable fractions. The total copper concentration in control soil, OECD soil, hare faecal matter and mine borne Acacia litter was 12(±0.01), 22(±2), 435(±47) and 645(±59) respectively. Scanning electron microscopic (ESEM) examinations revealed higher metal deposition in worm tissue exposed to faecal matter of hare. The bioaccumulation percent of worms exposed to copper mine litter with copper mine soil is in the order Cd (250%) >Zn (37.3%) > Cu (15.4%) > Pb (1.7%) and is consistent to earlier findings. There was no significant correlation between litter samples and concentration of metals in worm tissue. However, the bioavailability percent for copper in all samples are dominant except for Acacia pycnantha leaf litter being the lowest 90.9%. Earthworm reproduction test revealed that even with a high copper concentration in all samples, Eucalyptus camaldulensis litter produced the highest juvenile count (160%). Evidently, earthworms are seen to reproduce well even in contaminated litter irrespective of level of metal content. Our findings suggest that there are various risks associated with metal transfer and pollution through plant and animal litter in ecosystem and should be appropriately managed. Highlights: Feeding earthworms to mine site detritus system poses ecological risks. Eucalyptus camaldulensis litter produced highest juvenile count of 150%. Cu was most bioavailable in worm tissue exposed to hare faeces. Cd in copper mine litter is more vulnerable to bioaccumulation.